Weaving ways of knowing in practice: a collaborative approach to prioritizing community knowledge and values in wildlife camera monitoring with Magnetawan First Nation - Claire Kemp; Kathryn Yarchuk; Allyson Menzies; Nadine Perron; Samantha Noganosh; Joseph Northrup; Jesse Popp (Canadian Science Publishing, 2024)
There is not one singular way to weave together Indigenous and Western knowledges; creating meaningful cross-cultural collaborations requires a foundation of relationships rooted in the context of specific people and place. As interest in working across knowledge systems increases, our goal is to provide an example of respectful and appropriate cross-cultural collaboration within environmental practice. We demonstrate our collaborative, mixed-methods approach to developing a community-based wildlife monitoring program with Magnetawan First Nation that prioritizes community knowledge and values. Through community interviews and a youth sharing circle, participants highlighted values (respect, interconnection, reciprocity, collaboration, and relationship) as well as research priorities, providing examples of what each may look like in practice, to inform our monitoring approach. These examples, paired with reflections from the research team, are shared to explore the process of weaving together knowledge and values to co-create a community-based wildlife monitoring program, applying wildlife cameras as much more than simply a tool for data collection. This research provides tangible examples of weaving together knowledges and values in the context of environmental monitoring, helping guide future cross-cultural collaboration to ensure this work is being done in a good way.